Barriers and enablers to monitoring and deprescribing opioid analgesics for chronic non-cancer pain: protocol for a qualitative evidence synthesis using the Theoretical Domains Framework. Issue 11 (12th November 2019) - Cross, Amanda J; Buchbinder, Rachelle; Bourne, Allison; Maher, Christopher; Mathieson, Stephanie; Lin, Chung-Wei C; O'Connor, Denise A
Abstract : Introduction: The over-prescription and overuse of opioid analgesics for chronic non-cancer pain (CNCP) is a growing issue. Synthesis of evidence about the barriers and enablers to reducing long-term opioid prescribing and use will enable the development of tailored interventions to address both problems. Objective: To synthesise the barriers and enablers to monitoring the ongoing appropriateness of opioid treatment and deprescribing opioids for CNCP from the clinician, patient and general public point of view, and to map the findings to the Theoretical Domains Framework (TDF). Methods and analysis: We will perform a qualitative evidence synthesis using the TDF. We will include qualitative research that has explored clinician, patient and the general public's perceptions regarding barriers and enablers to monitoring and deprescribing opioids for CNCP. Studies will be identified via searches in MEDLINE, EMBASE, CINAHL, AMED and PsycINFO. Databases will be searched from inception to July 2019, and the studies must be published in English. Article selection and data extraction will be completed independently by two review authors. Methodological quality of included studies will be independently assessed by two review authors using the Critical Appraisal Skills Programme quality assessment tool. We will conduct thematic synthesis and then map identified themes and sub-themes to TDF domains. Confidence in synthesis findings will be evaluated using the Grading of Recommendations Assessment, Development, and Evaluation Confidence in the Evidence from Reviews of Qualitative Research tool. Ethics and dissemination: Ethical approval is not required to conduct this review. We will publish the results in a peer-reviewed journal. PROSPERO registration number: CRD42019140784